2022
DOI: 10.3389/fpsyt.2022.764368
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Treatment Effects Unrelated to Hair-Cortisol and Hair-BDNF Levels in Chronic Tinnitus

Abstract: BackgroundCurrently, there are no objective markers to measure treatment efficacy in chronic (distressing) tinnitus. This study explores whether stress-related biomarkers cortisol and brain-derived neurotrophic factor (BDNF) measured in hair samples of chronic tinnitus patients change after compact multimodal tinnitus-specific cognitive behavioral therapy.MethodsIn this longitudinal study, hair-cortisol and hair-BDNF levels, self-reported tinnitus-related distress (Tinnitus Questionnaire; TQ), and perceived st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
0
9
1
1
Order By: Relevance
“…In future, the field can expect further improvements in assessment and therapy. Novel research frameworks focus on dimensional (not categorical) conceptualizations of psychological distress 124 125 126 , biomarkers of tinnitus-related distress 33 35 127 as well as refined psychotherapeutic treatment frameworks 128 . In addition, the importance of unified data collections 129 130 131 or methodological advances in big data analysis are of increasing importance 31 58 .…”
Section: Discussionmentioning
confidence: 99%
“…In future, the field can expect further improvements in assessment and therapy. Novel research frameworks focus on dimensional (not categorical) conceptualizations of psychological distress 124 125 126 , biomarkers of tinnitus-related distress 33 35 127 as well as refined psychotherapeutic treatment frameworks 128 . In addition, the importance of unified data collections 129 130 131 or methodological advances in big data analysis are of increasing importance 31 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding treatment effects, we expected treatment-induced changes in tinnitus-related distress and psychological symptoms based on previous studies with the same or similar treatment interventions ( Seydel et al, 2010 , 2015 ; Brueggemann et al, 2018 , 2019 ; Basso et al, 2022a ), but no significant effects were observed. Neither stress and anxiety levels nor NK cell frequencies showed significant treatment-related changes.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were in-patients receiving treatment at the Tinnitus Center between July 2019 and March 2020, consisting of a short-term multimodal CBT-based treatment program specifically designed for chronic tinnitus lasting 4 to 5 days ( M = 4.59, SD = 0.5). The treatment included ENT and general medical examinations, education, counseling, individual and group CBT sessions, auditory attention training, relaxation, and physiotherapy ( Basso et al, 2022a ). The recruitment of new participants was stopped in spring 2020 due to the beginning of the COVID-19 pandemic; the completion of follow-up measurement sessions lasted until August 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline cortisol concentrations were shown to be higher in participants with tinnitus and high tinnitus-related distress in one study (Hébert et al, 2004). More recently, higher perceived tinnitus loudness was also reported to be associated with higher hair-cortisol levels (Basso et al, 2022). In contrast, in individuals with chronic tinnitus (≥6 months) a blunted cortisol response to psychosocial stress was found (Hébert and Lupien, 2007), as well as a hypersuppression of cortisol after administration of a low dose (0.5 mg) of dexamethasone, pointing to HPA axis hypofunction and to enhanced negative feedback to the HPA axis (Simoens and Hébert, 2012).…”
Section: Introductionmentioning
confidence: 93%